ERP Software Selection Strategy Using Analytic Hierarchy Process (AHP) Case Study: PT Gramedia Printing - FX Agung Pramanto; Erna Oktora; Ramlan Ramlan; Muhammad Drajat; Irfan Nasullah (Komunitas Dosen Indonesia, 2021)
Enterprise Resource Planning (ERP) is an integrated information system technology used by world-class manufacturers to improve company performance. According to the policy determined by Kompas Gramedia, in all business sectors, the strategy must implement ERP. Printing PT Gramedia plans to implement ERP. The ERP that will be implemented in the printing company has not yet decided which ERP to use. Persian Malan. The choice of ERP in PT Gramedia printing is the object of research. The research was conducted by applying quantitative research methods, using raw data and auxiliary data as samples. The test results and analysis are expected to provide guidelines for PT Gramedia's print management to choose the correct implementation of ERP, so as to realize the vision to be realized